A comparison of the reproductive strategies of key species of a prograding dune system in the Mlalazi Nature Reserve, Natal - Todd, Colleen Barbara (Rhodes University, Faculty of Science, Botany Department, 1995)
The succession on the dunes of the Mlalazi Nature Reserve represents a classical example of primary succession. The reproductive strategies of eight key species were compared to determine some of the mechanisms affecting the community dynamics, at the population level, in the early stages of succession. There is a temporal separation in the flowering and fruiting phenologies. Passerina rigida, Stipagrostis zeyheri and Imperata cylindrica produced small seeds with a low fruit/seed mass ratio within a short cycle. The seeds are suitable for wind-dispersal. The animal-dispersed species; Eugenia capensis, Mimusops caffra and Scaevola plumieri, produced large fleshy seeds with a high fruit/seed mass ratio within cycles of six months and more. Chrysanthemoides monilifera, also an animal-dispersed species, produced a large quantity of small fleshy seeds throughout the year. The fern, Microsorium scolopendrium produced spores throughout the year. The staggered fruiting and flowering phenology ensures a year-round availability of fruit in the dunefield. The key species formed less than half of the species composition of the soil seed bank. The size and range of the soil seed bank differed between the species. P. rigida and S. plumieri formed a high proportion of the seeds in the soil with a wide distribution along the successional gradient. The other species had low soil seed densities with short distribution ranges, or were not present. P. rigida and S. plumieri are easily dispersed species, whereas the other species may have a more restricted and clumped distribution due to the effect of foragers. A high density of P. rigida and E. capensis seeds were found under the parent trees. Only seeds of P. rigida and S. zeyheri were found in the soil in the open. Seeds of P. rigida, S. zeyheri, E. capensis and M. caffra were found under the canopies of P. rigida, E. capensis and M. caffra. No seeds of C. monilifera and I. cylindrica were found in the soil, possibly due to predation. The period of the study (September 1991 to November 1992) was in a dry or drought cycle with only 56.8% of the mean annual rainfall falling. Seed germination and seedling survival of all the species were affected by these dry, warm climatic conditions. The species had seedling densities of less than 4 seeds/mÂ². The environmental conditions along the successional gradient also had an effect on seed germination and seedling survival. Environmental factors of soil pH, light intensity and surface soil temperatures were higher in the open than under canopy. Soil pH and the understorey cover decreased as the light intensity decreased from under the canopy of P. rigida to M. caffra . Litter cover and plant height increased. E. capensis had measurements intermediate to the two species, but had higher surface soil temperatures and plant height than P. rigida. Seedlings of P. rigida in the open and under the canopy of the parent plants had died by the end of the monitoring period. 50% of the seedlings of S. zeyheri under the canopy of P. rigida and M. caffra died. The mortality rate of the seedlings of E. capensis was lower under M. caffra than under the parent plants. I. cylindrica may be propagated vegetatively. However, the mortality of the propagules was greater under the canopy of E. capensis than under P. rigida. M. caffra only germinated under the canopy of E. capensis with a 100% mortality of the seedlings. M. scolopendrium only produced propagules through vegetative propagation under the canopy of E. capensis and M. caffra. The mortality of the young ferns was less than 50% and less under M. caffra than under E. capensis. No seedlings of C. monilifera or S. plumieri were found. The seed distribution range, seed germination requirements and the effect of the environmental conditions on the germination of the seeds and seedling establishment of the species appear to important factors of the reproductive strategies regulating the size of the species populations along the successional gradient.
Keywords: Sand dune plants -- South Africa -- KwaZulu-Natal -- Mlalazi Nature Reserve; Sand dune plants Comparative studies